2024
DOI: 10.1136/oemed-2023-109100
|View full text |Cite
|
Sign up to set email alerts
|

Chronic occupational exposures to irritants and asthma in the CONSTANCES cohort

Guillaume Sit,
Laurent Orsi,
Yuriko Iwatsubo
et al.

Abstract: ObjectivesThe impact of chronic occupational exposures to irritants on asthma remains discussed. We studied the associations between occupational exposures and asthma, with specific interest for chronic exposure to irritants, including disinfectants and cleaning products (DCPs) and solvents.MethodsCross-sectional analyses included 115 540 adults (55% women, mean age 43 years, 10% current asthma) working at inclusion in the French population-based CONSTANCES cohort (2012–2020). Current asthma was defined by eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Exposure to certain substances in the workplace, such as irritants ( 47 ), chemicals, dust and fumes, can trigger asthma symptoms in adult life ( 48 ). The CONSTANCES cohort has shown that exposure to solvents and to irritants can trigger adult asthma ( 49 , 50 ).…”
Section: Other Risk Factors For Late Onset T2 Eosinophilic Asthmamentioning
confidence: 99%
“…Exposure to certain substances in the workplace, such as irritants ( 47 ), chemicals, dust and fumes, can trigger asthma symptoms in adult life ( 48 ). The CONSTANCES cohort has shown that exposure to solvents and to irritants can trigger adult asthma ( 49 , 50 ).…”
Section: Other Risk Factors For Late Onset T2 Eosinophilic Asthmamentioning
confidence: 99%